Investigations into the Causes and Control of theu Growth Arrestment Phenomenon of Sultana. I. Symptoms and Survey Results - Saayman, D. (South African Journal of Enology and Viticulture, 2017)
Growth abnormalities, locally called "growth arrestment phenomenon" (GAP), occurring in the Sultana vineyards in the Lower Orange River region were first described in 1955. Characteristically, single vines or patches of vines are affected, show poor budding, retarded shoot growth during flowering, localised blackening of peduncles and abortion of flower clusters, followed by vigorous renewed shoot growth and flower shatter. Shiny spots on the upper surface of basal leaves are associated with symptoms mentioned above. Because of flower cluster abortion and flower shatter, crop losses exceeding 800/o occurred on affected vines. An extensive survey and analysis programme revealed GAP to be mainly associated with low K values in soil and plants, a low irrigation frequency, especially during the dormancy period, and relatively heavy textured soils.